Stabilization by Nano Spray Dryer of Pioglitazone Polymeric Nanosystems: Development, In Vivo, Ex Vivo and Synchrotron Analysis - Marcelle Silva-Abreu; Esther Miralles; Christina S. Kamma-Lorger; Marta Espina; María Luisa García; Ana Cristina Calpena (MDPI AG, 2021)
Pioglitazone-loaded PLGA-PEG nanoparticles (NPs) were stabilized by the spray drying technique as an alternative to the treatment of ocular inflammatory disorders. Pioglitazone-NPs were developed and characterized physiochemically. Interaction studies, biopharmaceutical behavior, ex vivo corneal and scleral permeation, and in vivo bioavailability evaluations were conducted. Fibrillar diameter and interfibrillar corneal spacing of collagen was analyzed by synchrotron X-ray scattering techniques and stability studies at 4 °C and was carried out before and after the spray drying process. NPs showed physicochemical characteristics suitable for ocular administration. The release was sustained up to 46 h after drying; ex vivo corneal and scleral permeation profiles of pioglitazone-NPs before and after drying demonstrated higher retention and permeation through cornea than sclera. These results were correlated with an in vivo bioavailability study. Small-angle X-ray scattering (SAXS) analysis did not show a significant difference in the organization of the corneal collagen after the treatment with pioglitazone-NPs before and after the drying process, regarding the negative control. The stabilization process by Nano Spray Dryer B-90 was shown to be useful in preserving the activity of pioglitazone inside the NPs, maintaining their physicochemical characteristics, in vivo bioavailability, and non-damage to corneal collagen function after SAXS analysis was observed.